Response of the European Union on Return Directive and Readmission Agreements (RDRAs) on Nigerian Irregular Migrants - Irabor, Peter (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2023)
This study appraised the EU RDRAs on Nigerian irregular migrants and examined the challenges of RDRAs on Nigerian irregular migrants. The study made use of primary sources of data through in-depth interview conducted on EU delegation to Nigeria and ECOWAS, European External Action Service, Frontex, International Organisation for Migration, Idia Renaissance, Nigeria Immigration Service and the National Agency for the Prohibition of Trafficking in Persons. Findings from the study showed that two types of return directive exits; voluntary return and enforced return. Voluntary returnees are provided with Assisted Voluntary Return and Reintegration (AVRR) while enforced returnees are not provided with AVRR, and they are likely detained, escorted by the policemen through the back door and corridor of the airport and deported to Nigeria or transit countries. Findings from the study showed the challenges of RDRAs on Nigerian irregular migrants in that, most return carried out by the EU are not in compliance with the laid down regulation as some migrants are return to countries of transit. Moreover, the conditionality attached to readmission agreements are only applicable for highskilled migrants, a situation described as brain drain for Nigeria and brain gain for the EU. The study concluded that EU RDRAs are restrictive in nature which provide escape routes for irregular migrants in European countries, and that lack of compliance on RDRAs are the results of unlawful detention of Nigerian irregular migrants by the EU as well as torture and abuse by the security officials and traffickers, a situation that violate human rights. W niniejszym artykule dokonano oceny unijnej dyrektywy powrotowej i umowy o readmisji (RDRA) oraz wskazano wyzwania z nimi związane w kontekście nigeryjskich nielegalnych migrantów. W badaniu wykorzystano pierwotne źródła danych, jak pogłębione wywiady przeprowadzone z delegacją UE w Nigerii i ECOWAS, Europejską Służbą Działań Zewnętrznych, Frontexem, Międzynarodową Organizacją ds. Migracji, Idia Renaissance, Służbą Imigracyjną Nigerii i Krajową Agencją ds. Zakazu Handlu Ludźmi. Wyniki badania wykazały, że istnieją dwa rodzaje powrotów: powrót dobrowolny i powrót przymusowy. Osoby powracające dobrowolnie otrzymują pomoc w powrocie i reintegracji (AVRR), podczas gdy osoby powracające przymusowo nie otrzymują takiej pomocy, przeważnie są zatrzymywane, eskortowane przez policjantów na lotnisko i deportowane do Nigerii lub krajów tranzytowych. Badanie wyszczególniło również wyzwania związane z implementowaniem RDRA wobec nigeryjskich migrantów o nieuregulowanym statusie, ponieważ większość powrotów przeprowadzanych przez UE nie jest zgodna z ustanowionymi przepisami, gdyż niektórzy migranci są odsyłani do krajów tranzytowych. Co więcej, warunki związane z umowami o readmisji mają zastosowanie tylko do wysoko wykwalifikowanych migrantów, co jest określane jako “drenaż mózgów” dla Nigerii i “pozyskiwanie mózgów” dla UE. W badaniu stwierdzono, że unijne przepisy RDRA mają restrykcyjny charakter, co skutkuje powstawaniem dróg ucieczki dla nielegalnych migrantów w Europie, a brak zgodności z przepisami RDRA jest wynikiem bezprawnego przetrzymywania nigeryjskich nielegalnych migrantów przez UE, a także tortur i nadużyć ze strony funkcjonariuszy bezpieczeństwa i handlarzy ludźmi, co stanowi naruszenie praw człowieka.
Odpowiedź Unii Europejskiej w sprawie dyrektywy powrotowej i umów o readmisji (RDRA) dotyczących nielegalnych migrantów z Nigerii
Keywords: European Union; Irregular Migrants; Migration; Return Directive and Readmission Agreements; Unia Europejska; nielegalni migranci; migracja; dyrektywa powrotowa i umowy o readmisji